Public Versus Private Pension System: Albanian Case - Hysa, Eglantina (Mediterranean Journal of Social Sciences, 2012)
In most of the countries, in these last years, pension reforms are a real challenge for the governments. There exist four maincriteria classifying and categorizing pension systems around the world: 1- Who manages the system (public / private); 2- How thecoverage is decided (Employment-related / Universal and Means-tested); 3- How benefits are calculated (defined contribution / definedbenefit); 4- How benefit are financed (PAYG / Fully Funded).This study focuses in these criteria, by comparing the public and private pension systems in general terms. A special focus is also givento the Albanian case and recommendations for the future reforms take place.